Vegetation structure and species composition of agarwood (Aquilaria spp.) habitats in natural and planted forests in Buru Island, Indonesia - NINGSIE INDAHSUARY UAR; LINA KARLINASARI; ISKANDAR Z. SIREGAR; SETYO PERTIWI (Society for Indonesian Biodiversity, 2025)
Abstract. Uar NI, Karlinasari L, Siregar IZ, Pertiwi S. 2025. Vegetation structure and species composition of agarwood (Aquilaria spp.) habitats in natural and planted forests in Buru Island, Indonesia. Biodiversitas 26: 3927-3939. Aquilaria is a genus of agarwood-producing trees that grow almost throughout Indonesia. Buru Island is one of the areas with the presence of Aquilaria spp. species. Currently, information related to the structure and composition of tree species in the habitats of agarwood plants is still limited. This study aimed to describe the structure and composition of tree species in the natural habitat and cultivated area of agarwood plants in three locations in Buru Island, namely Airbuaya, Fena Leisela, and Batabual Sub-districts. Vegetation analysis was carried out by field surveys using a combination of line transect and square plot methods to document plant species and number of individuals at seedling, sapling, pole and tree levels. The results showed that the stand structure of vegetation community at the research location formed an inverted